Pemahaman Aturan Pajak, Kesadaran Wajib Pajak, Kualitas Pelayanan Pajak Dan Kepatuhan Pelaku E-Commerce di Karesidenan Surakarta - Nur Rohmah, Safitri; Chotidjah, Erna; Okfitasari, Antin (ITB AAS Indonesia Surakarta, 2024)
The aim of this study is to empirically show the effect of understanding tax rules, awareness of taxpayers and quality of tax services on e-commerce compliance. Online trading is inseparable from a tax known as the e-commerce tax. This research method uses a descriptive approach, by collecting data from questionnaires and literature. The data used are primary data by using a Likert scale questionnaire on e-commerce actors in Karasidenan Surakarta. The results of the study prove that understanding of tax rules affects compliance with e-commerce actors, taxpayer awareness does not affect compliance with e-commerce actors and the quality of tax services affects compliance with e-commerce actors.